AN ANALYSIS OF PERSONIFICATION IN ROBERT FROST’S POEMS: personification - Helena Naul; Novi Sriwulandari (Fakultas Sastra Universitas Gresik, 2022)
This research investigated the personification in Robert Frost’s poems. The researcher analyzed five poems; The Road not Taken, My November Guest, Stopping by Woods On Snowy Evening, Mending Wall and Storm Fear. This research is descriptive qualitative particularly document research. The source this research was several of Robert Frost’s poems. The data were in the form of sentences gained by doing several step. The first step was reading the poems. The second was understanding the poems. The third was underlining the phrase that contained of personification. The next step was identifying the data. After that, in analyzing the data, the researcher classified the sentences into personification and interpreted them. In conclusion, the researcher found of personification in the collected of Robert Frost’s poems; The Road Not Taken has a sentence. My November Guest has a sentence. Stopping by Woods on Snowy Evening has two sentences. Mending Wall has two sentences. Storm Fear has two sentences.